PENURUNAN ANGKA PEROKSIDA MINYAK KELAPA TRADISIONAL DENGAN ADSORBEN ARANG SEKAM PADI IR 64 YANG DIAKTIFKAN DENGAN KALIUM HIDROKSIDA - Sri Wahjuni; Betty Kostradiyanti (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2008)
Research on IR64 rice shell ash activation with KOH was carried out. Then, this activated ash known asadsorbent was applied to absorb H2O2 solution. This adsorbent was then applied to absorb peroxide number oftraditional coconut oil.The research includes activation of rice ash with 5%, 10%, and 15% KOH, followed by determination ofrate and isotherm adsorption towards H2O2. Finally, the ash was applied to absorb traditional coconut oil, in order todecrease peroxide number of the oil.Research results indicated that, adsorption rate of the ash with KOH activation is higher than without KOHactivation. Adsorption isotherm patern of the ash with and without activation is following Langmuir adsorption. Riceshell ash activated with 15% KOH can increased adsorption capacity of H2O2 about 297.16 mg/g, whereas withoutactivation the adsortion capacity is about 271.66 mg/g. Activated ash with 15% KOH was the applicated to decreaseperoxide number of traditional coconut oil. In this study, we obtain that the ash can decreased peroxide number until84.4%.